OPTIMALISASI BANTARAN SUNGAI DAN SOSIALISASI KETAHANAN PANGAN SERTA PROGRAM IKLIM UNTUK MENINGKATKATKAN CITRA WISATA DI KELURAHAN SUKAPURA - Makky Wachyudi; Muthi’ah Aryuni; Agus Irfan; Rama Rizki Ardiansyah; Alvina Aulia; Tiara Nurfiana Dewi; Monica Indriani (Swadaya: Indonesian Journal of Community Empowerment, 2021)
Community service activities carried out in the Sukapura village area, especially in RW 01 and RW 07, namely analyzing the tourism potential in the area with survey methods and mentoring throughprocurement and outreach targeting all RW leaders and elements of LKK Sukapura where there are 2 The theme that was delivered in stages in the extension of the Potential Extension program (PEPOTA) was about food security and the climate program (PROKLIM) which was delivered by the Food, Agriculture, Maritime Affairs and Forestry Department of DPPKP and the Cirebon City Environment Service (DLH) by being able to provide hope for understanding to the community. the community in order to optimize the existing potential in order to increase tourism in the Attitude area can have more value and be known to many people Adaptation of additional implementation evaluation methods from the application of the Climate Program (PROKLIM) in every RW in Sukapura Village Keywords : River bank, food security,climate program, touristimage